ORGANIZATION OF ADMINISTRATION IN CENTRAL ASIA AND KAZAKHSTAN MUSLIMS OFFICE (1943-1991) - Temurbek Abramatov; Qurbonnazarov Azizbek (American Journals Publishing, 2024)
This article deals with the organization of management in the Central Asia and Kazakhstan Muslim Office. Based on scientific data, the author studied and analyzed the specific aspects of the organization of management in the office of Muslims in Central Asia and Kazakhstan on the basis of available literature.
Keywords: Central Asia, Kazakhstan, Muslim office, Islam.